Hurdels to cross for the ’jadibuti’ cultivation of Nepal: A case study of Karnali, Midwestern Nepal - Rai, S. K. (Journal of Plant Resources, 2009)
No abstract available. <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–>Bulletin of the Department of Plant Resources Vol 30, 2008 pp 105-108